An interacting quantum atom study of model SN2 reactions (X–···CH3X, X = F, Cl, Br, and I). Issue 10 (10th November 2017) - Alkorta, Ibon; Thacker, Joseph C. R.; Popelier, Paul L. A.
Abstract : The quantum chemical topology method has been used to analyze the energetic profiles in the X –  + CH3 X → XCH3  + X – SN 2 reactions, with X = F, Cl, Br, and I. The evolution of the electron density properties at the BCPs along the reaction coordinate has been analysed. The interacting quantum atoms (IQA) method has been used to evaluate the intra‐atomic and interatomic energy variations along the reaction path. The different energetic terms have been examined by the relative energy gradient method and the ANANKE program, which enables automatic and unbiased IQA analysis. Four of the six most important IQA energy contributions were needed to reproduce the reaction barrier common to all reactions. The four reactions considered share many common characteristics but when X = F a number of particularities occur. © 2017 Wiley Periodicals, Inc. Abstract : The quantum chemical topology method has been used to analyze the energetic profiles in the X –  + CH3 X → XCH3  + X – SN 2 reactions, with X = F, Cl, Br, and I. The evolution of the electron density properties at the BCPs along the reaction coordinate has been analysed. The interacting quantum atoms (IQA) method has been used to evaluate the intra‐atomic and interatomic energy variations along the reaction path. The different energetic terms have been examined by the relative energy gradient method and the ANANKE program, which enables automatic and unbiased IQA analysis.